Parent artery occlusion for ruptured aneurysms in moyamoya vessels or on collaterals - Zhou, Zibo; Xu, Kan; Yu, Jinlu (Frontiers in Neurology, 2023)
Background Aneurysms in moyamoya vessels or on collaterals are difficult to treat. Parent artery occlusion (PAO) via endovascular treatment (EVT) is often the last resort, but the safety and efficacy of this approach need to be evaluated. Materials and methods A retrospective study was performed on patients admitted to our hospital who were diagnosed with unilateral or bilateral moyamoya disease (MMD) associated with ruptured aneurysms in moyamoya vessels or on collaterals. These aneurysms were treated with PAO, and the clinical outcome was recorded. Results Eleven patients were aged 54.7 ± 10.4 years, and six patients were male (54.5%, 6/11). The aneurysms in 11 patients were single and ruptured, and the average size was 2.7 ± 0.6 mm. Three (27.3%, 3/11) aneurysms were located at the distal anterior choroidal artery, 3 (27.3%, 3/11) were at the distal lenticulostriate artery, 3 (27.3%, 3/11) were at the P2–3 segment of the posterior cerebral artery, 1 (9.1%, 1/11) was at the P4–5 segment of the posterior cerebral artery, and 1 was at the transdural location of the middle meningeal artery. Among the 11 aneurysms, PAO by coiling was performed on 7 (63.6%, 7/11), and Onyx casting was performed on 4 (36.4%, 4/11). Of 11 patients, 2 (18.2%, 2/11) suffered intraoperative hemorrhagic complications. During follow-up, all patients had good outcomes with a modified Rankin scale score of 0–2. Conclusion As a last resort, the application of PAO with coiling or casting Onyx for ruptured aneurysms in moyamoya vessels or on collaterals may be safe with an acceptable clinical outcome. However, patients with MMD may not always achieve expected health outcomes, and PAO for the aneurysm can bring only temporary relief.